Ki Hajar Dewantara's Philosophy of Education in the Perspective of Oumar Muhammad Al-Toumy Al-Syaibani and Its Implications of Islamic Education - Ahmad, Agus; Setiawan, Dedi; Mushodiq, Agus (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This research aims to analyze Ki Hajar Dewantara's educational philosophy as contained in the Philosophers of Education trilogy